SOSIALISASI DAN IMPLEMENTASI SISTEM INFORMASI TANGGAP DARURAT BENCANA ALAM KOTA MEDAN - Hrp, Abdul Chaidir; Wijaya, Rian Farta; Sukrianto, Sukrianto; Ardya, Dwika; Helmy, Ahmad; Mentari, Siti (Smart Education, 2025)
Abstract: The city of Medan is one of the regions in North Sumatra that is vulnerable to natural disasters such as floods, fires, and extreme weather events. Limited access to accurate information, low community preparedness, and the absence of integrated disaster information systems remain major challenges in disaster risk reduction efforts. This community service activity aims to improve community preparedness and response capacity through the socialization and implementation of a web-based Disaster Response Information System for Medan City. The methods used include problem identification, system development, socialization, training, and system implementation involving community representatives and local stakeholders. The results indicate an increase in community understanding of disaster mitigation and emergency response procedures, as well as the utilization of the information system as a medium for early warning, reporting, and coordination. The implementation of the disaster response information system is proven to support faster information dissemination and strengthen community participation in disaster management efforts. Keywords: disaster mitigation; information system; community service; disaster response; Medan City Abstrak: Kota Medan merupakan salah satu wilayah di Provinsi Sumatera Utara yang memiliki tingkat kerawanan tinggi terhadap bencana alam seperti banjir, kebakaran, dan cuaca ekstrem. Keterbatasan akses informasi yang akurat, rendahnya kesiapsiagaan masyarakat, serta belum terintegrasinya sistem informasi kebencanaan menjadi permasalahan utama dalam upaya pengurangan risiko bencana. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kesiapsiagaan dan kapasitas tanggap bencana masyarakat melalui kegiatan sosialisasi dan implementasi Sistem Informasi Tanggap Bencana berbasis web di Kota Medan. Metode pelaksanaan meliputi identifikasi masalah, pengembangan sistem, sosialisasi, pelatihan, dan implementasi sistem dengan melibatkan perwakilan masyarakat dan pemangku kepentingan lokal. Hasil kegiatan menunjukkan adanya peningkatan pemahaman masyarakat terhadap mitigasi bencana dan prosedur tanggap darurat, serta pemanfaatan sistem informasi sebagai media peringatan dini, pelaporan kejadian, dan koordinasi. Implementasi sistem informasi tanggap bencana terbukti mendukung percepatan penyebaran informasi dan memperkuat partisipasi masyarakat dalam penanggulangan bencana. Kata kunci: mitigasi bencana; sistem informasi; pengabdian masyarakat; tanggap bencana; Kota Medan